Layered and integrated medical countermeasures against Burkholderia pseudomallei infections in C57BL/6 mice - Klimko, Christopher P.; Shoe, Jennifer L.; Rill, Nathaniel O.; Hunter, Melissa; Dankmeyer, Jennifer L.; Talyansky, Yuli; Schmidt, Lindsey K.; Orne, Caitlyn E.; Fetterer, David P.; Biryukov, Sergei S.; Burtnick, Mary N.; Brett, Paul J.; et al. (Frontiers in Microbiology, 2022)
Burkholderia pseudomallei, the gram-negative bacterium that causes melioidosis, is notoriously difficult to treat with antibiotics. A significant effort has focused on identifying protective vaccine strategies to prevent melioidosis. However, when used as individual medical countermeasures both antibiotic treatments (therapeutics or post-exposure prophylaxes) and experimental vaccine strategies remain partially protective. Here we demonstrate that when used in combination, current vaccine strategies (recombinant protein subunits AhpC and/or Hcp1 plus capsular polysaccharide conjugated to CRM197 or the live attenuated vaccine strain B. pseudomallei 668 ΔilvI) and co-trimoxazole regimens can result in near uniform protection in a mouse model of melioidosis due to apparent synergy associated with distinct medical countermeasures. Our results demonstrated significant improvement when examining several suboptimal antibiotic regimens (e.g., 7-day antibiotic course started early after infection or 21-day antibiotic course with delayed initiation). Importantly, this combinatorial strategy worked similarly when either protein subunit or live attenuated vaccines were evaluated. Layered and integrated medical countermeasures will provide novel treatment options for melioidosis as well as diseases caused by other pathogens that are refractory to individual strategies, particularly in the case of engineered, emerging, or re-emerging bacterial biothreat agents.